The role of inflammation in central serous chorioretinopathy: From mechanisms to therapeutic prospects - Shen, Xiao; Kong, Fanhua; Wen, Jing; Wang, Xiao; Huang, Chunlian (Frontiers in Pharmacology, 2024)
Central serous chorioretinopathy (CSC) is a leading cause of permanent vision loss, ranking fourth among macular diseases, trailing only age-related macular degeneration, diabetic retinopathy, and retinal vein obstruction. While mounting evidence implicates inflammation as a pivotal factor in the onset and advancement of CSC, the specific pathophysiological process and molecular mechanisms underlying inflammation remain incompletely understood. A complex network of cytokines, chemokines, and adhesion molecules interplay to trigger inflammatory and pathological cascades, highlighting the need for a comprehensive comprehension of the inflammation-related mechanisms behind CSC progression. In this piece, we examine the existing comprehension of CSC's pathology and pathogenesis. Additionally, we present an overview of the mechanisms underlying the onset and progression of CSC inflammation, followed by a thorough analysis and discussion of the potential of targeted inflammatory intervention for both preventing and treating CSC.